A survey of the situation of teaching and learning English among high schools in Can Tho city : - Lê, Thị Dạ Thảo (Can Tho University, 2008)
The study aims to find out the motivation in learning English among high school students, the students' performance in the national examination for the General Certificate of Secondary Education, students' difficulties in learning English, and what teaching method teachers used and what skill their focus was on.